Circulating free DNA integrity and concentration as independent prognostic markers in metastatic breast cancer - Cheng, Jie; Wallwiener, Markus; Surowy, Harald; Cuk, Katarina; Schott, Sarah; Sohn, Christof; Schneeweiss, Andreas; Burwinkel, Barbara (Breast cancer research and treatment, 2018)
PurposeNon-invasive blood-based molecular markers have been investigated for cancer diagnosis and prognosis. Circulating free or cell-free DNA (cfDNA) variables have been shown to be putative markers in breast cancer prognosis.MethodsHere, we investigated the potential prognostic ability of cfDNA concentration and cfDNA integrity (cfDI) in a study cohort of 268 patients by quantitative PCR. We compared cfDNA concentration and cfDI at baseline and after one cycle of therapy in metastatic breast cancer (MBC) patients.ResultsA significantly increased cfDI (P = 1.21E-7 for ALU and P = 1.87E-3 for LINE1) and decreased cfDNA concentration (P = 1.17E-3 for ALU and P = 1.60E-2 for LINE1) in both repetitive DNA elements after one cycle of therapy was observed. A multiple Cox regression model indicated that cfDI and cfDNA concentration can serve as independent prognostic markers in patients at baseline with HR (95% CI) of 0.70 (0.48-1.01) for ALU cfDI, 0.63 (0.44-0.92) for LINE1 cfDI, 2.44 (1.68-3.53) for ALU cfDNA concentration, and 2.12 (1.47-3.06) for LINE1 cfDNA concentration and after one cycle of therapy with HR (95% CI) of 0.59 (0.42-0.84) for ALU cfDI, 0.51 (0.36-0.74) for LINE1 cfDI, 1.59 (1.31-1.92) for ALU cfDNA concentration, and 1.30 (1.17-1.45) for LINE1 cfDNA concentration, respectively. By comparing integrated prediction error of different models, cfDNA variables were shown to improve the prognostic power of the CTC status.ConclusionsWe hereby show that cfDNA variables, especially in combination with other markers, can serve as attractive prognostic markers for MBC patients at baseline and during the systematic therapy.
Published online: 16 January 2018
Gesehen am 23.04.2019